Comparison of the educational system of the Islamic Republic of Iran with Japan in terms of educational policy. - Mehdi Askari; محمدحسن الهی منش; رضا پریزاد (سپهر سیاست, 2017)
Skill training is the key to sustainable development in each country, and now its special significance is not hidden by anyone. In this research, we have tried to describe this scientific issue with the scientific method Considering the fact that our research question is related to the comparison of policy-making skills of the Islamic Republic of Iran and Japan, and the reasons for the inefficiency of training in Iran, so many methods and models are widely discussed in this research(regard). We came to this conclude that Phillips' six methods are the best and most consistent. This means that we can provide a useful and systematic way of comparative education. So that we can systematically examine the requirements for a conceptual analysis of a problem, the separation of the variables under consideration, the development of the hypothesis, the re-examination of conceptual analysis based on the hat-vernis, and the examination of the generalizability of the findings. The results of this study are to highlight the importance of both countries to skills, to coordinate and formalize informal and formal education, and the kingdom and livelihood. The beginning of educational reform in a historical period and the increasing spread of these trainings in both countries are shared and market-oriented, flexible and targeted. The coordination of the private and public sector, and the existence of an independent and working policy institution from the points of differentiation between the two countries of Iran and Japan. This research is a descriptive-analytical method with a comparative approach.